2‐Fatty Acrylic Acids: New Highly Derivatizable Lipophilic Platform Molecules. (1st April 2014) - Zerkowski, Jonathan A.; Solaiman, Daniel K. Y.
Abstract: This paper reports the incorporation of an alpha‐methylene unit into fatty acid skeletons. Since the new olefin is conjugated with the carboxylate, it is susceptible to 1, 4‐(Michael) additions. We have used multifunctional thiols and amines for additions at the methylene. The resulting products possess clusters of functionality grouped at one end of a hydrophobic tail. These structural patterns will be of use in the design of new types of bio‐based surfactants and polymers. One particularly promising pattern of functionality that can be obtained through oxidation and reduction chemistry is a 2‐fatty 1, 2, 3‐propanetriol, or a lipophilized glycerol moiety.